Build A Koperasi Organization As A Big House Of Umkm In Tangerang City - Asep Sugara; MD Sukamto (Fakultas Bisnis, 2021)
This study aims to explain the existing conditions of out-of-pocket koperasi organization in Tangerang City and explain the pattern of synergism between urban village koperasi organization and UMKM, so as to create business competitiveness based on a sustainable populist economy by utilizing various potentials. The results showed that the existence of sub-district koperasi organization in Tangerang City still seemed forced and less able to synergize with existing UMKM. Koperasi organization should be able to become homes for UMKM by utilizing the potential that exists in the region as well as the penta helix model of cooperation. Koperasi organization and UMKM must also be able to utilize and use information and technology for business management and marketing of their products or services.